Challenges and prospects in the 6G-enabled Internet of Things ecosystem - Mina Asaduzaman; Ferdous Hossain; Tan Kim Geok (Institute of Advanced Engineering and Science, 2026)
The exponential growth of the Internet of Things (IoT) applications is revealing critical limitations in current fifth generation networks (5G), especially with respect to scalability, latency, energy efficiency and intelligent resource management. These concerns make sixth-generation (6G) communication systems a near-future solution to facilitate intelligent, autonomous, and sustainable IoT ecosystems by amalgamating artificial intelligence (AI), terahertz (THz) communication, edge intelligence, semantic communication, and ultra-reliable low-latency communication (URLLC). But the research environment regarding 6G enabled IoT is still fragmented with the non-existence of a common analytical framework. In this paper, we present a structured survey and taxonomy based analytical framework for the 6G enabled IoT ecosystem. It classifies the recent works into enabling technologies, intelligent architectures, emerging applications, deployment challenges and future research directions. The requisite advancements in technologies needed for future IoT infrastructures are also highlighted through a comparison of 5G and 6G capabilities. The results of the analysis indicate that 6G can contribute to a substantial improvement of IoT performance in smart cities, healthcare, industrial automation and control applications (manufacturing science), autonomous transportation and precision agriculture. However, issues concerning cybersecurity, interoperability, sustainability, spectrum management and infrastructure cost still remain. This study is expected to enable the development of secure, scalable, intelligent and sustainable next-generation IoT systems based on collaborative edge computing.